Pengaruh Perkembangan Sektor Teknologi Informasi Terhadap Perkembangan Sektor E-Commerce (Studi Kasus: Negara-Negara Asean 2015-2019) - Ahmad Dharu Athallah; Neli Aida; Asih Murwiati; Heru Wahyudi (Publikasi Indonesia, 2022)
This study aims to determine the effect of the development of the information technology sector on the development of the e-commerce transaction sector, analyze the variables that support the use of information technology such as the number of mobile phone users, the number of internet users and the number of broadband telephone users on the value of e-commerce transactions in countries. in ASEAN. This study uses secondary data. This research uses Fixed Effect Model (FEM) approach. The data analysis model used is panel data regression. The results of this study indicate that the variable number of internet users and the number of mobile phone users has a positive and significant effect on the value of e-commerce transactions in ASEAN countries. While the number of broadband telephone users has a positive but not significant effect on the value of e-commerce transactions in ASEAN countries.